Secondary School Teachers Perception on Certification Exam - Abdullayeva, Minaya; Mdluli, Bongumusa; Salimova, Sevinj (ADA University, 2025)
This study explores the perceptions of secondary school teachers about the teacher certification exam. Although teacher certification is generally meant to help teachers grow in their careers and improve the standard of education, there is no research done to find out what the experiences of teachers are about the exam. This study focuses on the real experiences, and a qualitative approach with a phenomenological design was used to understand the lived experiences of teachers. The target population was secondary schools in Baku, and a sample of 12-15 teachers who had taken the certification exam were interviewed. The interviews revealed that the exam was stressful and never took into account the long years of service for the experienced teachers, where some even mentioned that it was like they had to prove themselves all over again. For the younger teachers, it was the direct opposite as they saw the exam as an opportunity to improve their teaching techniques and use it as a tool for professional growth. The teachers further offered practical suggestions such as adapting the certification process based on teaching experience, teachers being offered support to prepare for the exam, and including classroom observations. The study finally revealed that even though certification has a huge potential, it still needs to be more supportive, balanced, and most importantly, it must be grounded in the real lives of teachers, as good education begins by listening to the voices of everyday classroom leaders
Keywords: Teacher certification -- Examinations -- Azerbaijan -- Baku; Teachers -- Attitudes -- Azerbaijan -- Baku; Teacher effectiveness -- Evaluation.; Educational tests and measurements -- Social aspects; Qualitative research -- Methodology -- Azerbaijan; Education